2016
DOI: 10.1177/0001839216674457
|View full text |Cite
|
Sign up to set email alerts
|

State Ownership and Firm Innovation in China: An Integrated View of Institutional and Efficiency Logics

Abstract: Does state ownership benefit or impede firm innovation? Extant studies offer contradicting perspectives and inconsistent empirical findings regarding this issue. This study develops an integrated view of institutional and efficiency logics by proposing that whereas state ownership enables a firm to obtain R&D resources, it makes the firm less efficient in utilizing the resources to generate innovation. The results of two longitudinal panel datasets of Chinese manufacturing firms show that state ownership posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
661
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 788 publications
(763 citation statements)
references
References 93 publications
16
661
3
3
Order By: Relevance
“…A large number of studies have used R&D expenditures divided by firm sales as a measure of R&D intensity that can be viewed as the input of firms' R&D activities (Lee and O'Neill 2003;Zhang et al 2007). Sales of new product sales has been used as an innovation performance measure (Berchicci 2013;Cassiman and Veugelers 2006;Escribano et al 2009;Love et al 2009;Kafouros et al 2015;Tsai 2009;Zhou et al 2016) because it represents the success of new or significantly improved products in the market. The census data provide information on revenue from new or significantly improved products that can be viewed as the output of firms' R&D activities.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A large number of studies have used R&D expenditures divided by firm sales as a measure of R&D intensity that can be viewed as the input of firms' R&D activities (Lee and O'Neill 2003;Zhang et al 2007). Sales of new product sales has been used as an innovation performance measure (Berchicci 2013;Cassiman and Veugelers 2006;Escribano et al 2009;Love et al 2009;Kafouros et al 2015;Tsai 2009;Zhou et al 2016) because it represents the success of new or significantly improved products in the market. The census data provide information on revenue from new or significantly improved products that can be viewed as the output of firms' R&D activities.…”
Section: Methodsmentioning
confidence: 99%
“…For transitional economies, Li et al (2013) SOEs can afford to engage in innovation due to resource slack. Zhou et al (2016) also found that state ownership enables firms to gain more resources to invest in R&D activities.…”
Section: Ownership Types and Firms' Innovation: Institutional Theory mentioning
confidence: 96%
See 2 more Smart Citations
“…Governments can help firms overcome some of these resource barriers by providing government resources (Inoue et al, ; K. Z. Zhou et al, ) to accelerate the absorption and utilization of knowledge embedded in external innovativeness. Indeed, research has found that governments in different countries, ranging from developed to developing, play an important role in filling the gap between inventors and external financiers by directly providing financial assistance and loans to inventors (Siegel, Wessner, Binks, & Lockett, ; Svensson, ) or by facilitating the growth of private venture capital firms to support innovative firms (Gompers & Lerner, ).…”
Section: Hypothesesmentioning
confidence: 99%